Un réseau de surveillance des littoraux face au changement climatique en milieu insulaire tropical : l’exemple de Mayotte - Matthieu Jeanson; Franck Dolique; Edward J. Anthony (VertigO)
The global change currently observed generates accelerated coastal erosion and contribute to the degradation of coral reefs and mangroves degradation. These phenomena are exacerbated on tropical islands hosting large coastal populations, and thus render these coasts and their societies very vulnerable. In this context, it seems fundamental to seek to understand the evolution of these tropical coastal environments in terms of these extreme events, the impacts of which coastal island societies will be brought to bear more and more often. Awareness of these impacts has prompted the establishment of an operational observatory aimed at monitoring the coastal dynamics in several French tropical islands including Mayotte. The aims of the project will be to observe, supervise and characterize the rhythms and the mechanisms of evolution, adaptation and resilience of tropical beaches in the face of extreme climate and wave events (cyclones, storms, surges, strong swells…) in order to develop and implement appropriate defence strategies and/or adaptation.